1985
DOI: 10.1001/jama.1985.03350260088032
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise Proteinuria in Humans

Abstract: Strenuous exercise induces profound changes in renal hemodynamics and the protein content of urine. Postexercise proteinuria seems to be directly related to the intensity of exercise, rather than to its duration. The pattern of proteins identified in urine collected after exercise is different from normal physiological proteinuria. Immunochemical techniques demonstrate that postexercise proteinuria is of mixed glomerular-tubular type when heavy exercise is involved. The origin of proteinuria after light exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
5

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 19 publications
4
59
0
5
Order By: Relevance
“…Exercise has often been associated with increased proteinuria, but this is generally associated with exhaustive bouts of exercise (19,20,48,49). Our data clearly indicate that our exercise protocol was not sufficiently intense enough to elicit such an increase.…”
Section: Discussionmentioning
confidence: 63%
“…Exercise has often been associated with increased proteinuria, but this is generally associated with exhaustive bouts of exercise (19,20,48,49). Our data clearly indicate that our exercise protocol was not sufficiently intense enough to elicit such an increase.…”
Section: Discussionmentioning
confidence: 63%
“…shows that the decrease of sodium and water excretion during strenuous exercise in spite of an unchanged GFR may be explained by high production of aldosterone and by the deviation of blood from the kidneys to other organs during exercise (11,17). Therefore, the model used in the present study does not discriminate between the direct and indirect effects of endurance training on renal sodium reabsorption.…”
mentioning
confidence: 82%
“…Studies on humans using PAH clearance have demonstrated a decrease in renal plasma flow after physical exercise which was related to exercise intensity (16,17). An explanation for this reduced flow could be the intrarenal blood flow distribution, leading to a drop in the rate of renal PAH extraction during exercise (17).…”
mentioning
confidence: 99%
“…Post-exercise proteinuria has been found in various sport disciplines but the highest level has been noticed after swimming training [6,7]. Proteinuria depends on the type of exercise and its intensity [3,8,9]. Among several proteins existing in urine, measured after the training, albumin was notably on the highest level.…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
“…Kidneys play a key role in the development of the post-exercise proteinuria [2]. An increase in the proteinuria during an intense physical exercise is caused by penetration of the plasma proteins into renal tubules [3]. Proteins, present in the urine after an exercise on SAGI may provide valuable information about the process of adaptation to the physical exercise.…”
Section: Introductionmentioning
confidence: 99%